(untitled) (The Pakistan Development Review, 1988)
This paper uses the Granger direct test to evaluate the causal relationship between growth in money supply and inflation in Pakistan. The historical period investigated extends from 1973 to 1985. The results of the test show that money growth had a significant impact on inflation during the period considered. In addition, there is some evidence at hand showing that inflation, too, affected money growth over the 1973- 1985 period. The empirical issue of the impact of money supply on rate of inflation continues to be a much debated topic. For example, Tumovsky and Wohar (1984) do not find any identifiable relationship between money supply and prices over the 1929- 1978 period in the U.S., while Benderly and Zwick (1985) find money supply affecting prices in the U,S, over the 1955-1982 period. Jones and Uri (1986) also find evidence of money supply influencing price level in the U.S. during the 1953- 1984 period. Studies• for other countries, e,g. Driscoll, Ford, and Mullineux (1985) for the U.K., invariably report similar conflicting results about the relationship between money supply and prices. While there are numerous empirical studies that have examined the causal relationship .between money supply and prices in developed countries, there are also several recent studies that have addressed this particular issue for developing countries. In one such study, Aghevli and Khan (1978) use the Haugh-Pierce test to investigate the causal relationship between money growth and inflation in Brazil, Colombia. the Dominican Republic, and Thailand. t The results of the tests show a feedback or bidirectional causality between money and inflation in all the four developing countries over the 1964-1974 period.